Calcaneal Tendon Plasticity Following Gastrocnemius Muscle Injury in Rat - Barin, Fabrício Reichert; de Sousa Neto, Ivo Vieira; Vieira Ramos, Graciele; Szojka, Alexander; Ruivo, Amanda Lima; Anflor, Carla Tatiana Mota; Agualimpia, José David Hurtado; Domingues, Allan Corrêa; Franco, Octávio Luiz; Adesida, Adetola B.; Durigan, João Luiz Quaglioti; Marqueti, Rita de Cassia (Frontiers in Physiology, 2019)
Cross-talk between skeletal muscle and tendon is important for tissue homeostasis. Whereas the skeletal muscle response to tendon injury has been well-studied, to the best of our knowledge the tendon response to skeletal muscle injury has been neglected. Thus, we investigated calcaneal tendon extracellular matrix (ECM) remodeling after gastrocnemius muscle injury using a rat model. Wistar rats were randomly divided into four groups: control group (C; animals that were not exposed to muscle injury) and harvested at different time points post gastrocnemius muscle injury (3, 14 and 28 days) for gene expression, morphological, and biomechanical analyses. At 3-days post injury, we observed mRNA-level dysregulation of signaling pathways associated with collagen I accompanied with disrupted biomechanical properties. At 14-days post injury, we found reduced collagen content histologically accompanied by invasion of blood vessels into the tendon proper and an abundance of peritendinous sheath cells. Finally, at 28-days post injury there were signs of recovery at the gene expression level including upregulation of transcription factors related to ECM synthesis, remodeling, and repair. At this time point tendons also presented with increased peritendinous sheath cells, decreased adipose cells, higher Young’s modulus, and lower strain to failure compared to the uninjured controls and all post injury time points. In summary, we demonstrate that the calcaneal tendon undergoes extensive ECM remodeling in response to gastrocnemius muscle injury leading to altered functional properties in a rat model. Tendon plasticity in response to skeletal muscle injury merits further investigation to understand its physiological relevance and potential clinical implications.